Rural land use planning in developed nations/ edited by Paul J. Cloke - Paul J. Cloke (ed.) (London, 1989)
Rural land is regarded as important as it represents the space and resource base for timber and food production, and so becomes an essential component in the political discourse over the strategic need for agricultural self-sufficiency, and over the economic necessity in the case of some nations to reproduce an export capacity in agricultural produce under rapidly changing trade conditions. This survey and comparative analysis aims to provide a deeper knowledge and understanding of the planning of rural land use at an international level, discussing issues including major land use conflicts, landscape conservation, rural land budgets, the nature of planned intervention at various levels, rural political climate and central-local state relations and activities.
Keywords: Land use